The World's Urban Forests History, Composition, Design, Function and Management - McBride, Joe R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The purpose of this book is to examine urban forests in cities around the world. It will ask questions about the history, composition, structure, and management of trees in urban areas. Data for this book was collected in 33 cities across broad geographical areas known as biomes. Constraints and opportunities imposed on urban forest composition, design, and management by the ecological characteristics of these biomes will be examined. The book will also address the cultural and historical factors that influenced the characteristics of urban forests around the world.
1. Introduction -- 2. Methods -- 3. Biomes, Human Settlement, and the Selection of Cities. 4. History -- 5. Composition -- 6. Design -- 7. Function -- 8. Management -- 9. Urban Forests, Biomes, and History -- 10. The Future of the Urban Forest.
Keywords: Landscape architecture; Human geography; Cities and towns -- History; Urban ecology (Biology).; Landscape Architecture; Human Geography; Urban History; Urban Ecology